2021
DOI: 10.3390/genes12060946
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Pediatric Obesity: A Review

Abstract: Obesity is a chronic disease, which needs to be early detected early and treated in order prevent its complications. Changes in telomere length (TL) have been associated with obesity and its complications, such as diabetes mellitus and metabolic syndrome. Therefore, we conducted a systematic review to summarize results of studies that have measured TL in children and adolescents with obesity. Fourteen studies aiming to assess TL in pediatric patients with either obesity or who were overweight were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(97 reference statements)
0
8
0
1
Order By: Relevance
“…This increase of spermatozoa telomere length leads to an increase of telomere length in embryos as well as inborn children. This parameter can confer a real advantage in terms of protection against some diseases like obesity 107,108 . Furthermore, the telomere length in children's chromosomes is strongly associated with the sperm telomere length 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This increase of spermatozoa telomere length leads to an increase of telomere length in embryos as well as inborn children. This parameter can confer a real advantage in terms of protection against some diseases like obesity 107,108 . Furthermore, the telomere length in children's chromosomes is strongly associated with the sperm telomere length 6 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings have led several authors to the conclusion that factors involved in or associated with these metabolic disorders, such as diet, lack of physical activities, chronic inflammation, and high oxidative stress, are responsible for accelerated telomere attrition [ 26 , 27 ]. Thus, according to this concept, short telomeres could theoretically be used as a biomarker to detect the cellular impact of metabolic disorders or even predict the response to obesity treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results observed in children with obesity and metabolic disorders indicate that the aforementioned links already exist during the very first years of life. A few other studies have observed links between short telomeres and obesity [ 12 , 28 , 37 ] as well as increased glucose levels in children [ 38 ]. A study also showed the link between early obesity (at age 6 months) and short telomeres measured 3 to 5 years later [ 39 ], although telomere length was not measured at the age of 6 months when obesity was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the telomere has been referred to as a “mitotic clock” [ 12 ] and telomere length has been construed as a measure of “biological age” [ 13 ]. Consistent with these considerations, peripherally measured TL has been shown to be associated with a wide range of disease and health morbidities in adults [ 14 28 ] and children [ 29 38 ] and has become a popular biomarker for stress and accelerated biological aging [ 10 , 35 , 39 45 ]. Thus, TL at birth and the course of TL shortening in blood or saliva may provide insight into associated between premature birth and future health trajectory.…”
Section: Introductionmentioning
confidence: 96%